Pengaruh Cadangan Devisa, Penanaman Modal Luar Negeri, Laju Inflasi, dan Tingkat Suku Bunga terhadap Nilai Impor di Indonesia - Al Rizal Sandi; Aditya Wahyu Pramana; Ahmad Nabih Taqiyuddin; Moh. Nuril Islam Abdillah (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This study aims to determine the effect of independent variables (Foreign Exchange Reserves, Foreign Direct Investment, Inflation Rate, and Interest Rate) on the dependent variable (Import Value) in Indonesia for the last five years. This study uses quantitative analysis with descriptive methods used to obtain empirical evidence of the effect of Foreign Exchange Reserves (X1), Foreign Direct Investment (X2), Inflation Rate (X3), Interest Rate (X4), and Import Value (Y). Panel data regression analysis was used with a significance level of 5%. The results showed that the variables of Foreign Exchange Reserves, Foreign Direct Investment, Inflation Rate, and Interest Rate had no significant effect on Import Value in Indonesia. Foreign Exchange Reserves, Foreign Direct Investment, Inflation Rate, and Interest Rate simultaneously have a significant effect on Import Value in Indonesia.